The Poetics of Mourning and the American Elegy in Walt Whitman's "When Lilacs Last in the Dooryard Bloom'd" (Journal of the College of Education for Women, 2017)
Walt Whitman adds a poetic twist to the relationship of man’s body, soul with the universe. His inspiration in writing his elegy, "When Lilacs Last in the Dooryard Bloom'd," draws on aesthetico-political resources. Major amongst these is his leaning towards the American Transcendentalist idea of the "Over-Soul". The basic topoi in his poems is thus his identification of nature with the soul of man. The idea of the Over-Soul sheds light on the three stages of human loss: suffering, despair, and compensation. Whitman witnessed two political events, the outbreak of the civil war and Abraham Lincoln's death, which were of a particular importance to his life and work: they helped him shape a form and thematic concerns of his own. Building on the architectonics of the traditional elegy, Whitman Emersonizes the poetics of the genre, as he incorporates Emerson's idea of the Over-Soul and the law of compensation. This is translated into the shift, in his elegy, from the personal to the impersonal; from the intense feeling of grief to the thought of reconciliation.